ANALYSIS OF CHECK-IN GUEST HANDLING MODEL BASED ON THE RESERVATION AT HOTEL MERCURE BALI NUSA DUA - Kadek Boby Mahardika; Ni Nyoman Triyuni; I Ketut Suarja; I Putu Budiarta (Politeknik Negeri Bali, 2018)
Front office is one of the most important part which is the absolute should be on an organization hotel .In every hotel the role and function of the front office could be clearly seen , especially on the activity of going in the area front desk .In the morning , walking guests who want to checking out in the lobby show the high trust and hope the reception guests on the services , cashiers and also porter .So will they be on the day and afternoon , visitors who will check-in very much hope that the process of check-in and they shall walk with fast and smoothly .As for also some differences that is conducted by employees front office in dealing with a guest check-in and to other sources of reservation. There are several the reservation kind of like an reservation from individuals ( personal ) account , the reservation of company , the reservation of online travel agents and offline travel agents .Handling the check-in will be the first impression for guests about how the quality of treatment a hotel .To see the extent to which the quality of handling check-in against the guests at Hotel Mercure Bali Nusa Dua , hence writers interested do research by the title analysis handling model guests check-in based on the reservation at the Hotel Mercure Bali Nusa Dua. In this research the use writers interview with as a source of primary data and source of such as books , the internet and journal as secondary data .The determination of key informants can be determined by dictates one who get to tell the story easily , understand to information needed , and happily inform researchers .Informants the research is for human resources manager , reservation manager and all the employees front office department at the Hotel Mercure Bali Nusa Dua and using data collection method as a method of observation , a method of interviews and the literature study .In this research analysis techniques the data used is a technique descriptive qualitative data analysis .It means , the data gathered during the survey described the details of the discussion compiled systematically.